Symbolic Restorative Justice in the Courtroom: Navigating the Intersection of Justice and Child Welfare in Indonesian Juvenile Court Decisions - Pancasilawati, Abnan; Herlambang, Saifuddin; Naffati , Abdel Kadir (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
Indonesian state law, particularly the Juvenile Criminal Justice System Law No. 11 of 2012, designates diversion as the primary mechanism for addressing children in conflict with the law. However, in practice, the majority of juvenile court judges continue to impose sanctions oriented toward imprisonment. This article examines the discrepancy between the statutory framework and its practical application by investigating the symbolic implementation of restorative justice in juvenile cases adjudicated by the Balikpapan District Court. It underscores the persistent tension between diversion-focused legal mandates and courtroom practices that remain entrenched in a retributive paradigm. Employing socio-legal research methods and John Braithwaite’s shaming theory, the study analyzes sixteen juvenile court decisions rendered in 2024. The findings reveal that cases involving child protection and narcotics offenses were almost invariably met with imprisonment, accompanied by symbolic interventions such as vocational training. In contrast, theft and negligence cases permitted more hybrid approaches that combined punitive and rehabilitative elements; nevertheless, these approaches failed to achieve substantive restoration. The analysis concludes that restorative justice within Balikpapan’s juvenile court system remains largely rhetorical, functioning as a normative signifier rather than an effective mechanism for healing. The article argues that meaningful reform requires strengthening diversion pathways, enhancing the role of independent facilitators, and integrating legal, cultural, and community-based values into a more inclusive and humanistic juvenile justice framework.